A stochastic model of carbon nanotube deposition in the airways and alveoli of the human respiratory tract - Sturm, Robert (Inhalation toxicology, 2016)
Context: In the past two decades, possible exposure of workers to nanoparticles has excited the attention of occupational medicine, resulting in the conception of related risk assessments. Although most nanoparticles have been categorized as hazardous substances in the meantime, their behavior in the human respiratory tract still bears some enigmas, which require clarification. Objectives: The study pursues the goal to provide detailed theoretical lung deposition data of carbon nanotubes (CNT) with various diameters and lengths. Besides a quantification of total and regional deposition, also airway generation-specific deposition has been subjected to the modeling process. Methods: Theoretical approach of CNT deposition in the human lungs has been conducted by assuming a stochastic structure of the bronchial network, within which particle transport takes place along randomly selected paths. Fluid-dynamic particle characteristics have been simulated by application of a rigid fiber model, which considers diverse forces and torques acting on the particles during their translocation within the inhaled air. Particle deposition in the entire lungs has been approximated by using the aerodynamic/thermodynamic diameter concept and related empirical deposition formulae. Results: Theoretical deposition data reflect a significant dependence of CNT deposition on (a) the effective size of the particles and (b) the conditions, under which they are taken up into the respiratory tract. Extremely small CNT (∼1 nm) are primarily filtered in the extrathoracic airways, intermediately sized CNT (∼10 nm) exhibit a preference to deposit in the alveoli, and large CNT (∼100 nm) are marked by minimum deposition. Conclusion: Pulmonary deposition of CNT is subject to a partly remarkable variation. According to the model of this study, particles of intermediate size seem to bear highest potential to act as hazardous substances.